(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The present study has attempted to explore educational aspirations of secondary school students having varying socio- economic backgrounds. A representative sample of 250 secondary students of class 10th was randomly selected from government and private high schools located in rural and urban areas of Howrah district West Bengal. Tools for collecting the data included Educational Aspiration Scale developed by Dr. V P Sharma and Dr. Anuradha Gupta (1980) and Socio-Economic Status Scale (SESS) by A.K Kalia and Sudhir Sahu (2012). The data were analyzed using descriptive, correlational and differential statistics. The finding of the study revealed that educational aspiration is significantly and positively related to socio- economic status of secondary school students. It is also found that there is a significance difference in case of (i) educational aspiration across gender and types of school and (ii) socio-economic status across locality and type of schools of secondary school students. However non-significant difference is observed in case of (i) socioeconomic status across gender and (ii) educational aspiration across locality of secondary school students. Interventions aimed at reducing the impact of socioeconomic inequalities should be given due considerations as it is associated with the level of educational aspiration of students. Addressing poverty of aspiration is necessary to build a society of fairness and opportunity. (Tessa Jowell, Secretary of State for Culture 2015).